2021
DOI: 10.1071/am20055
|View full text |Cite
|
Sign up to set email alerts
|

The myth of wild dogs in Australia: are there any out there?

Abstract: Hybridisation between wild and domestic canids is a global conservation and management issue. In Australia, dingoes are a distinct lineage of wild-living canid with a controversial domestication status. They are mainland Australia’s apex terrestrial predator. There is ongoing concern that the identity of dingoes has been threatened from breeding with domestic dogs, and that feral dogs have established populations in rural Australia. We collate the results of microsatellite DNA testing from 5039 wild canids to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…Dingoes can hybridize with modern dog breeds, and the genetic purity of dingoes varies across the continent [ 103 , 104 ]. For the purposes of our study, we have included dietary data for all free-roaming populations of dingoes, modern domestic dogs and their hybrids, hereafter collectively termed ‘dingoes', and have not tried to disentangle dietary studies according to the genetic purity of the source dingo population.…”
Section: Methodsmentioning
confidence: 99%
“…Dingoes can hybridize with modern dog breeds, and the genetic purity of dingoes varies across the continent [ 103 , 104 ]. For the purposes of our study, we have included dietary data for all free-roaming populations of dingoes, modern domestic dogs and their hybrids, hereafter collectively termed ‘dingoes', and have not tried to disentangle dietary studies according to the genetic purity of the source dingo population.…”
Section: Methodsmentioning
confidence: 99%
“…As semi-wild companions, they contributed to Aboriginal society as hunting assistants, waterfinders and guardians (Philip 2020). Despite this long association they retained their independence, remaining true to the description of wild living canines (Cairns et al 2021), not reliant on human society for food or water, and exerting influence as apex predator on local flora and fauna (Fig. 8).…”
Section: The Ecological Role Of the Dingomentioning
confidence: 99%
“…All wild canine populations in Australia are predominantly of dingo heritage (see "The myth of wild dogs in Australia: are there any out there?" Cairns et al 2021). Genetic testing indicates dingo populations in central Australia, and to the north and west of the continent, are largely free from introgression with domestic dogs.…”
Section: The Ecological Role Of the Dingomentioning
confidence: 99%
“…Predation by wild dogs (i.e. dingoes, see Cairns et al 2021) is documented by the NSW government as a threat (see DPIE 2021). Our modelling suggested that presence of the dingo had no influence on occupancy or detection of the black-striped wallaby.…”
Section: Conservation and Managementmentioning
confidence: 99%